Revitalization of Religious Values Through the Reinforcement of Local Culture-Based Character Education in Pasuruan Regency - Syaifulloh, Mashabib; Jamhuri, M.; Kirom, Askhabul (Pendidikan Agama Islam STIT Palapa Nusantara, 2025)
The weakening religious character among the community, especially the younger generation, is a major concern. Values such as honesty, responsibility, tolerance, and social care are degraded due to the lack of integration of local culture in character education. The purpose of this study is to analyze how local cultural practices, such as village purification rituals and earth alms, play a role as a reinforcement strategy in strengthening religious character values. This study uses a qualitative phenomenological approach, with data collection techniques through in-depth interviews, participatory observation, and documentation. The informants consisted of community leaders, religious leaders, and cultural actors. The results of the study show that local cultural practices have functionally become a means of reinforcing character values through habituation, symbolism, and social example. Reinforcement occurs informally but consistently, reinforcing religious values, cooperation, and responsibility in the community. The conclusion of the study revealed that the community independently formed an effective character education system without the intervention of formal institutions, making local culture an educational instrument with spiritual and contextual value. The implications of these findings show the importance of reconstructing the community-based character education model and local culture, as well as opportunities to integrate traditional values into the national education system in a more applicable and sustainable manner.